Transaction costs in healthcare: empirical evidence from Portuguese hospitals - Jiménez Victor; Afonso Paulo (Cogent Business & Management, 2023)
Transaction Cost Economics has been used in the healthcare context to discuss the make-or-buy dichotomy, focusing on minimizing production or governance costs, respectively. Nevertheless, it is important to recognize that there are other relevant costs, which influence these decisions in health care. Thus, the purpose of this research project was to study such additional variables which may significantly influence the dynamics of transaction costs in hospitals. Semi-structured interviewing was used to collect the data, complemented by some document analysis and observation in the visits made to the hospitals studied. The interviews were conducted during a period of three months, with directors and administrators of four Portuguese hospitals. A deeper study was developed in one of the hospitals where it was possible to get information from additional interviews and documents. Two important findings should be highlighted. Firstly, the internal transaction costs derived from the hospital's own internal contracting process which generates retention costs of medical personnel and costs of control of the internal contract itself. Secondly, they were studied the intangible costs, particularly those related to the decision of carrying out a process that could deteriorate the patient's health or her/his critical situation, making the total cost, including treatment and possible re-hospitalizations higher than the cost of having treated the patient internally since the initial cost was considered greater than treating the patient outside hospital facilities. These variables should be considered when studying or using TCE in hospitals, complementing and extending the traditional framework as it is discussed here.
Keywords: 650; cost management; healthcare management; organizational behavior; Portuguese hospitals; transaction costs